2021
DOI: 10.1021/jasms.1c00121
|View full text |Cite
|
Sign up to set email alerts
|

Absolute Quantitation of Tryptophan-Containing Peptides and Amyloid β-Peptide Fragments by Coulometric Mass Spectrometry

Abstract: Isotope-labeled internal standards are routinely used for mass spectrometry (MS)-based absolute quantitation. However, syntheses of isotope-labeled peptides are time-consuming and costly. To tackle this issue, we recently developed a coulometric mass spectrometric (CMS) approach for absolute quantitation without the use of standards, based on the electrochemical oxidation of cysteine or tyrosine-containing peptides followed by mass spectrometric measurement of the oxidation yield. To further expand the utility… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 38 publications
0
6
0
Order By: Relevance
“…Previously, we demonstrated that CMS can be used for absolute quantitation of a single protein based on quantitation of its surrogate peptides. , In this study, we explored the possibility for using CMS for quantitation of multiple proteins in a mixture in one run. We reason that this would be straightforward as long as multiple surrogate peptides representing different proteins could be LC-separated.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Previously, we demonstrated that CMS can be used for absolute quantitation of a single protein based on quantitation of its surrogate peptides. , In this study, we explored the possibility for using CMS for quantitation of multiple proteins in a mixture in one run. We reason that this would be straightforward as long as multiple surrogate peptides representing different proteins could be LC-separated.…”
Section: Resultsmentioning
confidence: 99%
“…As the protein can be enzymatically digested into peptides and the amount of peptide can reflect the quantity of its precursor protein, our CMS can also be used for absolute quantitation of proteins. However, previously, CMS was only used for the quantitation of single protein including mAb. ,, This study explored CMS for multi-protein quantitation in one mixture sample in the same run and demonstrated the potential of CMS for absolute quantitation of low-abundant HCP in the presence of high-abundant NIST mAb 8671, without using standards. In addition, by using CMS, this study presents simultaneous quantitation of native and deamidated peptides as well as the succinimide intermediate from deamidation of Asn 318 residue of NIST 8671 mAb, for the first time.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…In this study, to eliminate the need for using standards or calibration curves for quantitation, we present a new strategy of using electrochemistry-assisted mass spectrometry, namely coulometric mass spectrometry (CMS). We recently have applied our CMS method for direct absolute quantitation of organic compounds, peptides, and proteins. As illustrated in Scheme , our quantitation strategy involves the chemical reduction of N -nitrosamine to hydrazine.…”
Section: Introductionmentioning
confidence: 99%